Oncological and Reproductive Outcomes in Patients With Advanced-Stage Ovarian Immature Teratoma: Experience From a Tertiary Center - Wang, Dan; Cang, Wei; Zhu, Shan; Jia, Congwei; Cao, Dongyan; Yang, Jiaxin; Xiang, Yang (Frontiers in Oncology, 2022)
Objective: To evaluate the oncological and reproductive outcomes in patients with advanced-stage ovarian immature teratoma (IMT). Methods: We retrospectively reviewed the medical records of patients with advanced-stage IMT who were treated with surgery between January 1985 and December 2020. Fertility-sparing surgery (FSS) was defined as preservation of the uterus and at least one adnexa. Oncological outcomes were compared between patients who underwent FSS and radical surgery. Patients who underwent FSS were also contacted to gather information about their menstrual history and reproductive outcomes. Results: Forty-six patients fulfilled the inclusion criteria, of whom 38 underwent FSS and eight were treated with radical surgery. Fifteen patients suffered recurrence after a median follow-up time of 74.2 months (range: 4.1–434.1 months). The 5-year disease-free survival (DFS) and overall survival (OS) rates were 69.1% and 89.9%, respectively. Multivariate analysis identified suboptimal cytoreductive surgery as the only independent risk factor for recurrence. There was no significant difference in DFS or OS between patients with different surgical procedures. Ten of the 15 relapsed patients had optimal salvage surgery and all remained alive with no evidence disease. Among the 32 patients who underwent FSS, 29 resumed menstruation after surgery, and five of seven patients who designed pregnancy achieved a total of five successful pregnancies. Conclusions: Ovarian IMT has a favorable prognosis, even when diagnosed at an advanced stage. FSS is feasible in patients with advanced-stage IMT who wish to preserve their fertility. Patients may benefit from optimal cytoreductive surgery during initial and salvage surgery.